Hubungan Power Otot Tungkai Dengan Frekuensi Roundhouse Kick Atlet Mma Pogogul Kabupaten Buol Sulawesi Tengah - Zulkifli Lamusu; Mohamad Reza Pratama Diuli; Adrianto Labanga (-, 2026)
This study aimed to analyze the relationship between lower limb muscle power and the frequency of roundhouse kicks among male MMA Pogogul athletes in Buol Regency, Central Sulawesi. The study employed a quantitative method with a correlational approach. The population consisted of all male MMA Pogogul athletes in Buol Regency, totaling 9 athletes, all of whom were selected as the research sample using a total sampling technique. Lower limb muscle power was measured using the Standing Broad Jump test, while roundhouse kick frequency was assessed based on the number of kicks performed within 10 seconds. Data were analyzed using descriptive statistics and the Pearson Product-Moment Correlation test. The results revealed a correlation coefficient (r) of 0.624, indicating a positive relationship between lower limb muscle power and roundhouse kick frequency. These findings suggest that athletes with greater lower limb muscle power tend to perform roundhouse kicks at a higher frequency. However, the observed correlation did not reach statistical significance at the 5% significance level, as the calculated r value was lower than the critical r value. The coefficient of determination was 38.94%, indicating that lower limb muscle power contributed 38.94% to the variation in roundhouse kick frequency, while the remaining 61.06% was influenced by other factors, such as movement coordination, balance, flexibility, technical proficiency, and neuromuscular ability. Based on the findings, it can be concluded that lower limb muscle power has a positive relationship with roundhouse kick frequency, although the relationship is not statistically significant. These findings indicate that roundhouse kick performance is a multifactorial skill influenced by various physical and technical factors that interact simultaneously. Therefore, efforts to improve roundhouse kick performance should not only focus on enhancing lower limb muscle power but should also incorporate technical training, movement coordination, balance, flexibility, and speed endurance training.